Internet Addiction of Older Women and Its Relationship With Social Influence and Social Networks Use as a Mediator. (January 2023) - Rosell, Javiera; Leeson, George W.; Vergés, Alvaro
The aim is to analyse the relationship between social influence for Internet use and Internet addiction (IA) in older women, considering the use of Internet-based social networks as a mediator. The participants were 480 older women Internet users. Social influence, frequency of use of social networks and IA (including loss of control and emotional dysregulation) were evaluated. Structural Equation Modeling (SEM) was conducted to analyse the proposed model. The use of social networks was a significant mediator in the relationship between social influence for Internet use and the dimension of loss of control of IA. On the contrary, social network use was not a significant mediator. Older women with more social influence reported more frequency of social networking and, in turn, more loss of control in Internet use. Public policy and clinicians should address addictive behaviours about Internet use in older women, preventing the negative consequences.